2016
DOI: 10.3945/ajcn.115.129049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Internet-based, personalized nutrition randomized trial on dietary changes associated with the Mediterranean diet: the Food4Me Study

Abstract: Higher MedDiet scores at baseline were associated with healthier lifestyles and lower adiposity. After the intervention, MedDiet scores were greater in individuals randomly assigned to receive PN than in controls, with the addition of DNA-based dietary advice resulting in the largest differences in MedDiet scores. Although differences were significant, their clinical relevance is modest. This trial was registered at clinicaltrials.gov as NCT01530139.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
86
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 38 publications
(47 reference statements)
2
86
0
1
Order By: Relevance
“…Thus, a reduced set of standard clinical parameters allowing the identification of distinct metabolic subgroups may be useful in practice, for example, for effective targeted strategies for disease prevention at the metabotype subgroup level. [ 1,7,16–19 ] In previous work in an Irish cross‐sectional study in adults ( n = 875), named Irish National Adult Nutrition Survey (NANS), O'Donovan et al. [ 20 ] identified three metabolically distinct subgroups of individuals using k ‐means cluster analysis based on the four clinical standard serum parameters triacylglycerol (TAG), total cholesterol (TC), HDL cholesterol, and glucose.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a reduced set of standard clinical parameters allowing the identification of distinct metabolic subgroups may be useful in practice, for example, for effective targeted strategies for disease prevention at the metabotype subgroup level. [ 1,7,16–19 ] In previous work in an Irish cross‐sectional study in adults ( n = 875), named Irish National Adult Nutrition Survey (NANS), O'Donovan et al. [ 20 ] identified three metabolically distinct subgroups of individuals using k ‐means cluster analysis based on the four clinical standard serum parameters triacylglycerol (TAG), total cholesterol (TC), HDL cholesterol, and glucose.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was shown that gene-based personalized nutrition targeting the apolipoprotein E ( APOE ) gene was more effective in reducing saturated fat intake compared with standard dietary advice [34]. Also, greater Mediterranean diet scores were reported among participants who received gene-based personalized nutrition targeting specific variants in five nutrient-responsive genes compared with those who received dietary advice on the basis of current diet plus phenotype [35]. Furthermore, it was reported that disclosure of genetic information regarding angiotensin I converting enzyme ( ACE ) genotype for personalized nutrition resulted in greater changes in sodium intake compared to general population-based dietary advice [36].…”
Section: Genetic Background and Nutritional Prescriptionsmentioning
confidence: 99%
“…Increased understanding of gene-nutrient interactions may facilitate health and disease prevention (Casas et al, 2016; Corella et al., 2016;Celis-Morales et al, 2016). A growing market offers genetic tests "direct-toconsumer" as well as via healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
“…A growing market offers genetic tests "direct-toconsumer" as well as via healthcare professionals. The Food4me project has illustrated how personalized nutrition can be delivered online to the public (Celis-Morales et al, 2016). Tests can deliver information linking diet to health, lifestyle, weight or improved fitness (Covolo et al, 2015; Bloss et al, 2011).…”
Section: Introductionmentioning
confidence: 99%